Factors Associated with Early Introduction of Complementary Feeding (CF) - Marlina Marlina; Nadia Dwi Putri; Indah Trianingsih; Yusari Asih; Yeyen Putriana (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Early introduction of complementary feeding (MP-ASI) is the practice of providing additional food to infants before the age of six months, which contradicts the recommendations of the World Health Organization (WHO) and the Indonesian Ministry of Health (WHO, 2020). This practice may increase the risk of digestive disorders, infections, and nutritional problems in infants. WHO reports that only about 40% of infants worldwide receive exclusive breastfeeding, while the rest are introduced to complementary foods prematurely (WHO, 2021). The low rate of exclusive breastfeeding indicates that the practice of early MP-ASI is still prevalent. This phenomenon may be influenced by several factors, such as maternal knowledge, education, and employment status. Purpose: To identify the factors associated with early complementary feeding. Method: This research was a quantitative study with a cross-sectional design. The population included all mothers with infants aged 6–12 months in Marga Kaya Village. The sample consisted of 43 respondents selected using total sampling technique. Data were collected using questionnaires and analyzed using univariate descriptive analysis and bivariate analysis with the Chi-Square statistical test. Results: The results showed that most mothers introduced CF before six months of age (68.1%), with the majority having low knowledge (62.8%), low education (55.8%), and not working (67.4%). The Chi-Square test revealed a significant relationship between maternal knowledge (p = 0.001), education (p = 0.006), and employment (p = 0.022) and the practice of early CF. Conclusion: It can be concluded that there is a significant association between maternal knowledge, education, and employment and the practice of early complementary feeding. Suggestion: It is recommended that health workers enhance maternal education to ensure CF is provided at the appropriate recommended age.